2017
DOI: 10.1038/s41467-017-00335-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an insect-produced olfactory cue that primes plant defenses

Abstract: It is increasingly clear that plants perceive and respond to olfactory cues. Yet, knowledge about the specificity and sensitivity of such perception remains limited. We previously documented priming of anti-herbivore defenses in tall goldenrod plants (Solidago altissima) by volatile emissions from a specialist herbivore, the goldenrod gall fly (Eurosta solidaginis). Here, we explore the specific chemical cues mediating this interaction. We report that E,S-conophthorin, the most abundant component of the emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 67 publications
(84 reference statements)
6
63
1
Order By: Relevance
“…We found that exposure of M. persicae to β-ocimene also impaired their feeding behavior through shortening the total feeding period and phloem ingestion and increasing the frequency of stylet puncture. Consistent with these observation, it has previously been shown that treatment with the insect-produced volatile E , S -conophthorin significantly reduced the feeding mass of Solidago altissima ( Helms et al, 2017 ). Furthermore, exogenous application of chemical deterrents and exposure of nitric oxide also exhibited an impaired feeding behaviors like delayed or failed to reach phloem vessels ( Dancewicz et al, 2008 ; Gabryś et al, 2015 ; Woźniak et al, 2017 ).…”
Section: Discussionsupporting
confidence: 78%
“…We found that exposure of M. persicae to β-ocimene also impaired their feeding behavior through shortening the total feeding period and phloem ingestion and increasing the frequency of stylet puncture. Consistent with these observation, it has previously been shown that treatment with the insect-produced volatile E , S -conophthorin significantly reduced the feeding mass of Solidago altissima ( Helms et al, 2017 ). Furthermore, exogenous application of chemical deterrents and exposure of nitric oxide also exhibited an impaired feeding behaviors like delayed or failed to reach phloem vessels ( Dancewicz et al, 2008 ; Gabryś et al, 2015 ; Woźniak et al, 2017 ).…”
Section: Discussionsupporting
confidence: 78%
“…This GLV‐induced priming comes at a cost for the plants as it reduced growth rates (Engelberth and Engelberth, ). Other interesting findings are that touch‐induced volatiles can synchronize defences in neighbouring plants (Markovic et al ., ) and that goldenrod ( Solidago altissima ) responds to ( E , S )‐conophthorin, a volatile produced by a specialist herbivore, the goldenrod gall fly ( Eurosta solidaginis ) (Helms et al ., ). This brings another dimension to the field of plant−herbivore interactions.…”
Section: Molecular Mechanisms Underlying Voc Perceptionmentioning
confidence: 97%
“…Invertebrate herbivores and their natural enemies, for example, are often attracted to chemical cues associated with their host plants or prey (Badenes‐perez, Gershenzon, & Heckel, ; Mccormick et al, ; Wiskerke, Dicke, & Vet, ). Relatively recent work has also revealed plant detection of herbivore‐associated cues, including volatiles from herbivore‐damaged plants and compounds from herbivores themselves, with plants responding by inducing or priming their defences (Helms et al, ; Hu & Erb, ; Manosalva et al, ; Orrock et al, ). The roles of semiochemicals from plants and herbivores, particularly in above‐ground systems, have been fairly well characterized, whereas below‐ground chemical cues and cues from natural enemies have received less attention.…”
Section: Introductionmentioning
confidence: 99%